Prospective comparative study between conservative and interventional managements of high-grade renal trauma: Our experience in a tertiary care hospital - Partha Protim Mondal; Rajkumar Singha Mahapatra; Shiva Manohar Dutta; Arif Mahammad (Asian Journal of Medical Sciences, 2025)
Background: Trauma is the leading cause of morbidity and mortality globally, with blunt abdominal trauma more common than penetrating injuries. Renal injury accounts for 5% of all trauma cases and 24% of abdominal solid organ injuries. Advances in imaging, hemodynamic monitoring, and management techniques have enabled successful conservative management strategies for renal preservation. Aims and Objectives: This study aims to assess clinical presentation, demographic profiles, mechanisms of injury, complications, management, and outcomes in renal trauma cases. Material and Methods: This retrospective study included 62 patients diagnosed with renal trauma between December 2022 and July 2024. Patients were divided into two groups: Conservative management (Group 1) and interventional management (Group 2). Clinical variables, management strategies, and outcomes were analyzed. The study followed ethical standards approved by the responsible committee. Statistical analysis was performed using SPSS version 21, with P < 0.05 considered significant. The Chi-square test was used for categorical variables and Student’s t-test for numerical variables. Results: Blunt trauma (90.3%) was the most common, primarily due to motor vehicle accidents (46.8%). Hematuria was present in 85.5% of cases. Most injuries were Grade IV (43.5%) and Grade V (9.7%). Of Grade IV injuries, 77.8% were managed conservatively. Complications included urinary tract infection, hematuria, hypertension, and urinoma, all classified as Clavien grade 1-3. The success rate of conservative management was 100% for Grade III, 84% for Grade IV, and 66.7% for Grade V injuries. Conclusions: Conservative management is effective for most renal injuries, even in Grade IV and V cases, reducing the need for nephrectomy and hospital stay, while minimizing morbidity and mortality.